Modeling the Ecological Impact of Phosphorus in Catchments with Multiple Environmental Stressors. Issue 5 (12th September 2019) - Glendell, Miriam; Palarea‐Albaladejo, Javier; Pohle, Ina; Marrero, Shasta; McCreadie, Brian; Cameron, Graeme; Stutter, Marc
Abstract : The broken phosphorus (P) cycle has led to widespread eutrophication of freshwaters. Despite reductions in anthropogenic nutrient inputs that have led to improvement in the chemical status of running waters, corresponding improvements in their ecological status are often not observed. We tested a novel combination of complementary statistical modeling approaches, including random‐effect regression trees and compositional and ordinary linear mixed models, to examine the potential reasons for this disparity, using low‐frequency regulatory data available to catchment managers. A benthic Trophic Diatom Index (TDI) was linked to potential stressors, including nutrient concentrations, soluble reactive P (SRP) loads from different sources, land cover, and catchment hydrological characteristics. Modeling suggested that SRP, traditionally considered the bioavailable component, may not be the best indicator of ecological impacts of P, as shown by a stronger and spatially more variable negative relationship between total P (TP) concentrations and TDI. Nitrate‐N ( p < 0.001) and TP ( p = 0.002) also showed negative relationship with TDI in models where land cover was not included. Land cover had the strongest influence on the ecological response. The positive effect of seminatural land cover ( p < 0.001) and negative effect of urban land cover ( p = 0.030) may be related to differentiated bioavailability of P fractions in catchments with different characteristics (e.g., P loads from point vs. diffuse sources) as well as resilience factors such as hydro‐morphology and habitat condition, supporting the need for further research into factors affecting this stressor–response relationship in different catchment types. Advanced statistical modeling indicated that to achieve desired ecological status, future catchment‐specific mitigation should target P impacts alongside multiple stressors. Core Ideas: Soluble reactive P (SRP) alone was not the best indicator of diatom response. Total P (TP) association with diatoms was more spatially variable than SRP. Nitrate‐N and TP have a combined negative effect on the ecological response. Seminatural land use had the most important influence on ecological response. We recommend catchment‐specific mitigation of multiple stressors.